Model Akuntansi Sederhana Bagi UMKM (Studi Kasus Pada Panglong Muslim Laut Dendang Percut Sei Tuan) - Rapika Rapika; Kusmilawaty Kusmilawaty (Universitas Muhammadiyah Sumatera Utara, 2022)
The purpose of this service activity is to provide competency direction and understanding in determining and compiling income statements for UMKM at Muslim Panglong. This is carried out to help solve the problems faced by UMKM owners regarding their lack of understanding of accounting. Service activities are devoted to assisting in the preparation of income statements. The service program is carried out in several stages, starting with material presentation, practical simulation using the